Burkholderia pseudomallei in a lowland rice paddy: seasonal changes and influence of soil depth and physico-chemical properties - Lacombe, Guillaume; Ribolzi, Olivier; Rochelle-Newall, E.; Dance, D.A.B.; Manivanh, L.; Pierret, A.; Rattanavong, S.; Kounnavongsa, O.; Buisson, Y.; Elliott, I.; Maeght, J.L.; Xayyathip, K.; et al. (Springer, 2017)
Melioidosis, a severe infection with the environmental bacterium Burkholderia pseudomallei, is being recognised increasingly frequently. What determines its uneven distribution within endemic areas is poorly understood. We cultured soil from a rice field in Laos for B. pseudomallei at different depths on 4 occasions over a 13-month period. We also measured physical and chemical parameters in order to identify associated characteristics. Overall, 195 of 653 samples (29.7%) yielded B. pseudomallei. A higher prevalence of B. pseudomallei was found at soil depths greater than the 30 cm currently recommended for B. pseudomallei environmental sampling. B. pseudomallei was associated with a high soil water content and low total nitrogen, carbon and organic matter content. Our results suggested that a sampling grid of 25 five metre square quadrats (i.e. 25 × 25 m) should be sufficient to detect B. pseudomallei at a given location if samples are taken at a soil depth of at least 60 cm. However, culture of B. pseudomallei in environmental samples is difficult and liable to variation. Future studies should both rely on molecular approaches and address the micro-heterogeneity of soil when investigating physico-chemical associations with the presence of B. pseudomallei.